2020
DOI: 10.1177/1363461520906008
|View full text |Cite
|
Sign up to set email alerts
|

Key expressions of trauma-related distress in Cambodian children: A step toward culturally sensitive trauma assessment and intervention

Abstract: More than half of all children in Cambodia experience direct abuse and over 70% experience other traumatic events, which significantly increase their risks for a range of physical and mental health problems. Additionally, Cambodian children face longstanding sociopolitical, intergenerational, and cultural factors that compound the impact of other trauma. As a result, rates of posttraumatic stress symptoms among Cambodian youth are high. However, care providers often rely on Western-based nosology that does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…Religio-cultural practices, teachings, and ceremonies permeate child and caregiver responses in the current sample, including how children conceptualize, express, and cope with adverse life experiences and distress. This fits within a large body of cultural research in Cambodia and with Cambodian refugees that highlight religio-cultural belief systems as central to how Khmer people understand and express mental health problems (Bertrand, 2005; Chhim, 2013; Figge et al, 2020a; Hinton et al, 2002, 2005, 2019). For older populations, the reinstitution of Khmer Buddhist practices and beliefs is critical for shared healing following elimination of Buddhism and widespread violations of Buddhist rituals during the Khmer Rouge era (Kent, 2006), which is reflected in the various roles children in the current sample play in religio-cultural ceremonies and practices.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Religio-cultural practices, teachings, and ceremonies permeate child and caregiver responses in the current sample, including how children conceptualize, express, and cope with adverse life experiences and distress. This fits within a large body of cultural research in Cambodia and with Cambodian refugees that highlight religio-cultural belief systems as central to how Khmer people understand and express mental health problems (Bertrand, 2005; Chhim, 2013; Figge et al, 2020a; Hinton et al, 2002, 2005, 2019). For older populations, the reinstitution of Khmer Buddhist practices and beliefs is critical for shared healing following elimination of Buddhism and widespread violations of Buddhist rituals during the Khmer Rouge era (Kent, 2006), which is reflected in the various roles children in the current sample play in religio-cultural ceremonies and practices.…”
Section: Discussionsupporting
confidence: 69%
“…Current data were collected as part of a larger study of child posttraumatic stress symptoms and clinician perspectives in Cambodia (Figge et al, 2020a). All study materials and procedures were approved by DePaul University’s Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies focusing on child and adolescent mental health in Cambodia have shown high rates of depressive symptoms in young people [40] and high exposure to trauma [41]. The prevalence of epilepsy in a cross-sectional study was found to be 5.8 per 1000 [42].…”
Section: Open Accessmentioning
confidence: 94%
“…In Cambodia, significant work has taken place to describe Cambodian culture-bound syndromes and idioms of distress, particularly relating to trauma in both adults [ 43 45 ] and children [ 41 , 46 ]. Examples described in Cambodia include “baksbat” (broken courage) [ 47 ] “kut chraen” (thinking too much) [ 21 , 41 , 47 , 48 ] “mour mao” (easily angered) in children [ 41 ] and “khyal” (windlike substance) attacks (in Cambodian refugees) [ 49 ]. The importance of contextualised mental health research has been highlighted as crucial to developing accurate diagnostic criteria, effective interventions and appropriate long-term follow up [ 43 , 45 , 47 , 50 ].…”
Section: Introductionmentioning
confidence: 99%